New Antiadhesive Hydrophobic Polysiloxanes - Maria Nowacka; Anna Rygała; Dorota Kręgiel; Anna Kowalewska (Molecules, 2021)
Intrinsic hydrophobicity is the reason for efficient bacterial settlement and biofilm growth on silicone materials. Those unwelcomed phenomena may play an important role in pathogen transmission. We have proposed an approach towards the development of new anti-biofilm strategies that resulted in novel antimicrobial hydrophobic silicones. Those functionalized polysiloxanes grafted with side 2-(carboxymethylthioethyl)-, 2-(n-propylamidomethylthioethyl)- and 2-(mercaptoethylamidomethylthioethyl)- groups showed a wide range of antimicrobial properties towards selected strains of bacteria (reference strains Staphylococcus aureus, Escherichia coli and water-borne isolates Agrobacterium tumefaciens, Aeromonas hydrophila), fungi (Aureobasidium pullulans) and algae (Chlorella vulgaris), which makes them valuable antibacterial and antibiofilm agents. Tested microorganisms showed various levels of biofilm formation, but particularly effective antibiofilm activity was demonstrated for bacterial isolate A. hydrophila with high adhesion abilities. In the case of modified surfaces, the relative coefficient of adhesion for this strain was 18 times lower in comparison to the control glass sample.